2022
DOI: 10.3390/biom12101426
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Alphabet of Disorder—Glu and Asp Act Differently on Local but Not Global Properties

Abstract: Compared to folded proteins, the sequences of intrinsically disordered proteins (IDPs) are enriched in polar and charged amino acids. Glutamate is one of the most enriched amino acids in IDPs, while the chemically similar amino acid aspartate is less enriched. So far, the underlying functional differences between glutamates and aspartates in IDPs remain poorly understood. In this study, we examine the differential effects of aspartate and glutamates in IDPs by comparing the function and conformational ensemble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…The converse was also true, as replacing the relatively few D residues in the linker region with E residues (LR_DtoE) also reduced the helical content. However, LR_DtoE maintained more helicity than LR_E-toD, which is consistent with a recent study suggesting that glutamate helps maintain helicity, while aspartate helps maintain extended structures in IDPs (Roesgaard et al, 2022). This trend partially carried over to positively charged residues as well, with our LR_RtoK variant showing reduced helical content, while the helical content of the LR_KtoR variant remained more or less consistent with that of the wild-type linker region.…”
Section: Sequence Identity Of Charged Residues In the Cahs D Linker P...supporting
confidence: 91%
“…The converse was also true, as replacing the relatively few D residues in the linker region with E residues (LR_DtoE) also reduced the helical content. However, LR_DtoE maintained more helicity than LR_E-toD, which is consistent with a recent study suggesting that glutamate helps maintain helicity, while aspartate helps maintain extended structures in IDPs (Roesgaard et al, 2022). This trend partially carried over to positively charged residues as well, with our LR_RtoK variant showing reduced helical content, while the helical content of the LR_KtoR variant remained more or less consistent with that of the wild-type linker region.…”
Section: Sequence Identity Of Charged Residues In the Cahs D Linker P...supporting
confidence: 91%
“…Studies have shown that small differences in amino acid chemistries are of immense significance . As a result, Ser and Thr are not always interoperable, nor are Arg and Lys, ,, Glu and Asp, ,, Gln and Asn, or Phe and Tyr . Any interoperability is highly sequence- or context-specific .…”
Section: Overall Summary and Conclusionmentioning
confidence: 99%
“…Thus, of the proteins with lysine deserts longer than 200 residues (after Shannon filtering for low-complexity regions) in the yeasts S. cerevisiae and S. pombe , we found by manual curation that 7 out of 14 (50%) and 17 out of 35 (48%), respectively, are UPS components (Supplemental file 3). The previously described budding yeast lysine desert proteins Slx5 and San1 [ 17 , 18 ] were the highest scoring hits in S. cerevisiae (Supplemental file 3) [ 28 , 29 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the lysine deserts in the San1 and Slx5 E3s are localized in intrinsically disordered regions (IDRs) [ 17 , 18 ]. Therefore, we next analyzed the top 200 human lysine desert proteins for intrinsic disorder within the lysine deserts, noting that lysines in general are modestly enriched in IDRs [ 28 , 29 ]. Using the MobiDB database [ 30 ] annotation of intrinsic disorder, the average disorder for proteins in the human proteome was 26%, or 0.26 ± 0.23 (mean ± standard deviation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation